Palladium-catalyzed alkynylative [5 + 1] carboannulation of 1, 3-diarylprop-2-yn-1-yl acetates with terminal alkynes enabled by C–H functionalization. Issue 5 (2nd February 2022) - Yu, Jiang-Xi; Wu, Li-Jun; Wang, Zhi-Qiang; Xu, Zhi-Feng; Li, Jin-Heng
Abstract : Using 1, 3-diarylprop-2-yn-1-yl acetates as the five-carbon components enables alkynylative[5 + 1] carboannulation involving C–H functionalization toward 3-ethynyl-1-methylene-1, 2-dihydronaphthalenes. Abstract : A new method for the synthesis of 3-ethynyl-1-methylene-1, 2-dihydronaphthalenes via copper-promoted palladium-catalyzed intermolecular alkynylative [5 + 1] carboannulation of 1-arylphenyl-prop-2-yn-1-yl acetates involving C–H functionalization is described. Two terminal alkyne molecules serve as an alkynylation reagent and a one-carbon unit to enable alkynylative [5 + 1] carboannulation with excellent selectivity control, broad substrate scope and good tolerance of functional groups.